Оценка ущерба от абразионных риск-процессов на водных объектах Республики Беларусь - Levkevich, Виктор; Kobyak, Валерий; Pastukhov, Сергей; Kukshinov, Михаил; Buzuk, Александр (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2008)
We presented here the method for assessment of the abrasion damage on the tanks of the Republic of Belarus.